Policy, Research and Practice to Improve Student Outcomes: Some Philosophical Problems - John Clark (New Zealand Journal of Teachers' Work)
If policy, research and practice are to improve student outcomes, then the successful achievement of this will require prior attention to several fundamental philosophical problems. Failure to address these is likely to lead to a breakdown in the link between means and ends with the goals being sought coming to nothing. First, what, conceptually, is meant by ‘student outcomes’? Second, since not all student outcomes are educationally worth cultivating, judgement is required to determine which outcomes to promote and which not. Third, how are we to ascertain whether there is an improvement in student outcomes? Finally, if policy, research and practice are to improve student outcomes, it is incumbent on those promoting such policy, research and practice to empirically demonstrate how these causally bring about such improvement rather than any improvement being attributed to some other causal mechanism. This paper will critically examine these philosophical difficulties.